'I always get to see a film no matter what': a discourse on multiplexing in post-socialist Czechia. Issue 3 (2nd September 2017) - Hanzlík, Jan
ABSTRACT: The article focuses on the introduction of multiplexes to Czechia through a discourse analysis of articles in the Czech daily press related to multiplexing and government reports from the years 1996 to 2011. The text summarises the historical context of multiplexing in the West and theoretical works on multiplexing published to date. The subsequent part, methodologically based on the discourse analysis as delineated by Charles Acland, explores how multiplexes were constructed in Czech newspapers and reports published annually by the Ministry of Culture of the Czech Republic.